PERSEPSI SISWA CIBI TERHADAP FAKTOR LINGKUNGAN SEKOLAH YANG MEMPENGARUHI PRESTASI BELAJAR DI SMA NEGERI 1 PADANG - MARIATUL AKBAR (Universitas Negeri Padang, 2015)
AbstractThe background of this research is the difficulty a child read the word vowels. Smart Reading method is a method of learning to read without spelling to children easy, fast, effective and fun. The purpose of this study is to prove the effectiveness of smart methods to improve reading ability to read words vowels. This type of research is Single Subject Research with ABA design. The results showed an effective reading smart method to improve reading skills of children said vowels difficulty reading at SDN 01 Limau Manis Padang. Keyword: Star Reading; Smart reading of method; Difficult read